Development of Simplified Diabetes Nutrition Education Tools for Patients with Type 2 Diabetes Mellitus in Basrah, Iraq - Saman Hashim; Nada Al jassim; Abbas Mansour (International Journal of Nutrition Sciences)
Background: Effective patient education is an essential component in management of type 2 diabetes mellitus (T2DM). This study aimed to develop simplified Diabetes Nutrition Education Tools (SDNETs) to educate patients with T2DM.Methods: The study began with a published need assessment study. SDNETs were developed guided based on Health Belief Model theory, literature reviews and guidance from a panel of reviewers recruited for content validity. Then, face validity, readability, and acceptability were assessed using a 14-item Health Literacy (HL) scale and the Suitability Assessment of Materials (SAM) instrument in 30 patients with T2DM.Results: Internal reliability was assessed using Cronbach’s α (0.72, n=30), while test-retest reliability (0.86, n=30) was evaluated utilizing Pearson correlation. SDNETs had a HL score of 57.1% indicating the readability and acceptability among the patients. The SAM instrument’s score was 85% indicating the SDNET curriculum’s suitability.Conclusion: The Iraqi-based culture-integrated plate method was the most straightforward and comprehensive technique in the SDNET curriculum. The SDNETs were determined to be a valid and reliable tool for improving glycemic control through diabetes nutrition education among patients with T2DM in Basrah, Iraq.